A multi-site coronary sampling study on CRP in non-STEMI: Novel insights into the inflammatory process in acute coronary syndromes. (November 2018) - Damen, Sander A.J.; Cramer, Gilbert E.; Dieker, Hendrik-Jan; Gehlmann, Helmut; Aengevaeren, Wim R.M.; Oude Ophuis, Ton J.M.; Fokkert, Marion J.; Dikkeschei, Lambert D.; Vroemen, Wim H.M.; Verheugt, Freek W.A.; Brouwer, Marc A.; Suryapranata, Harry
Abstract: Background and aims: Inflammation has become a key element in cardiovascular disease, and recently, new anti-inflammatory interventions have shown promising results. In this context, CRP levels have been thoroughly studied in vitro and in animals, but studies in humans are scarce and insights into its release, site(s) of production and uptake are not uniform. Methods: We performed a biomarker study with multi-site sampling in the coronary circulation, in non-ST elevation MI (NSTEMI) patients with coronary angiography and right-sided catheterisation. Trans-lesional gradients were obtained by sampling distal to the culprit lesion, in patients with a suitable anatomy. To asses trans-cardiac gradients, blood was sampled from the systemic circulation, coronary sinus (CS) and great cardiac vein. Concentrations of CRP were measured with a high-sensitivity assay. Results: In 42 patients, a median systemic venous CRP concentration of 4.97 mg/L was observed. There was no evidence of a trans-lesional gradient (4.59 mg/L versus 4.56 mg/L, p = 0.278; n = 14). A significant decrease in CRP concentration was observed between systemic arterial and CS samples (4.88 mg/L versus 4.44 mg/L; p < 0.001; n = 42). This trans-cardiac gradient was irrespective of time of presentation, infarct size and culprit lesion location. The gradient was not only driven by blood that ran through the injured myocardium, but also by lower CRP concentrations in the coronary veins that drain non-infarcted myocardium. Conclusions: In the context of NSTEMI, we observed a trans-cardiac decrease in CRP, which may indicate the first human in vivo proof of a net CRP uptake by the myocardium, with a role for CRP both in the injured and adjacent myocardium. Highlights: In NSTEMI patients, there was a trans-cardiac decrease in CRP across the myocardium. This decrease was irrespective of time of presentation, infarct size and culprit lesion location. There was no trans-lesional gradient across the culprit coronary artery lesion. Both injured and non-injured myocardium contributes to the decrease in CRP.